Feel Home - Cultuurcentrum Strombeek Grimbergen (Grimbergen : Cultuurcentrum Strombeek Grimbergen, 2010)
Arad, Ron ; Bey, Jürgen ; Carretero, Julien ; Charlier, Jacques ; De Cock, Jan ; Deleu, Luc ; Gillick, Liam ; Grobelny, Pawel ; Grzeszykowska & Smaga ; Knoebel, Imi ; Beka Productions - Koolhaas Houselife ; Kwangho Lee ; Matta-Clark, Gordon ; Merz, Mario ; Muller, Fien ; Judd, Donald ; Pesce, Gaetano ; Philips, Karl ; Ruthenbeck, Reiner ; Steenhoudt, Stef ; Uecker, Günther ; Van Balen, Tuur ; Van Imschoot, Jan ; Van Kerckhoven, Anne-Mie ; West, Franz ; Willenz, Sylvain ; Wu, Tony
Nederlands
Exhibition. Feel Home. Grimbergen. Cultuurcentrum Strombeek Grimbergen. 2010-04-09. 2010-05-10
boek